Optimized AAA procedure of integration of mobile IP and SIP - XU Peng; LIAO Jian-xin; ZHU Xiao-min; WU Jia-chun (Tongxin xuebao)
In a multi-protocol,multi-layer mobility management scheme,mobile IP and SIP were used as mobility man-agement protocol in network layer and application layer,respectively.It was very inefficient when performing AAA op-erations in mobile IP and SIP independently.To solve this problem,proposed an optimized scheme,named Optimized AAA Procedure of Integration of Mobile IP and SIP（OAPIMS）.Under the new AAA protocol,DIAMETER,it optimized signaling procedure of the two protocols while performing mobility registration.So it reduced time of round trips of sig-naling exchange and improved efficiency.Analysis indicates that this scheme can reduce signaling cost,time delay and improve system performance significantly.